THE WAY OF RECOVERY OF TECHNOLOGICAL AUXILIARIES FOR HOT FORMING - V. E. Liventsev; V. N. Fedulov (Литьë и металлургия)
The ways of recovery of the technological auxiliaries for hot forming are given.